Pengembangan E-kamus Biologi Materi Klasifikasi Tumbuhan Dicotyledoneae Pada Kelas X SMA Negeri 4 Muaro Jambi: (Development of an E-Dictionary of Biology for Classification of Dicotyledoneae Plants in Class X SMA Negeri 4 Muaro Jambi) - Wuryan T Indriyani; Muswita Muswita; M. Erick Sanjaya (BIODIK, 2022)
This study aims to develop an e-dictionary as a medium for learning material classification of living things that has been feasible according to experts, and to find out the perceptions of teachers and students of class X SMA after using the developed media. Development research by referring to the 4D (Four-D) model with the stages of Define, Design, Develop and Disseminate due to time constraints, the research was only carried out until the develop stage. The product developed was validated by material experts and media experts, then assessed by a biology subject teacher for class X MIA SMA N 4 Muaro Jambi. The data used are qualitative and quantitative data, obtained from the results of the analysis of the calculation of questionnaires and interviews. Material expert validation was carried out three times with the percentage of the first stage obtained 46.87% included in the "not good" category, the second stage with a percentage of 71.87% in the "good" category and the third stage obtained a percentage of 76.56% in the category "very good". The media expert validation was also carried out three times, with the percentage of the first stage getting 53.12%, the second stage getting a percentage of 62.5% included in the "good" category, and the last stage the percentage obtained as much as 87.5% in the "very good" category. good". From the results obtained, it can be concluded that the e-dictionary media for the classification of Dicotyledoneae plants that has been developed is feasible to be used as an auxiliary media in the learning process of the classification of living things. Key words: e-dictionary, Website, plant classification Dicotyledoneae AbstrakÂ  Penelitian ini bertujuan untuk mengembangkan e-kamus sebagai media pembelajaran materi klasifikasi makhluk hidup yang telah layak menurut para ahli, serta mengetahui persepsi guru dan peserta didik kelas X SMA setelah menggunakan media yang dikembangkan. Penelitian pengembangan dengan mengacu pada model 4D (Four-D) dengan tahapan Define (pendefinisian), Design (perancangan), Develop (pengembangan), dan Disseminate (penyebaran) karena keterbatasan waktuÂ  maka penelitian hanya dilakukan sampai pada tahap develop (pengembangan). Produk yang dikembangkan divalidasi oleh ahli materi dan ahli media, kemudian dilakukan penilaian oleh guru mata belajaran biologi kelas X MIA SMA N 4 Muaro Jambi. Data yang digunakan ialah data kualitatif dan kuantitatif, yang diperoleh dari hasil analisis perhitungan angket dan wawancara. Validasi ahli materi dilakukan sebanyak tiga kali dengan persentaseÂ  tahap pertamaÂ  diperoleh 46,87% termasuk dalam kategori â€œtidak baikâ€ tahap ke-2 dengan persentase 71,87% kategori â€œbaikâ€ dan tahap ke-3 didapatkan persentase sebesar 76,56% kategori â€œsangat baikâ€. Validasi ahli media juga dilakukan sebanyak tiga kali, dengan persentase tahap pertama didapatkan 53,12%, tahap ke-2 diperoleh persentase 62,5% termasuk kedalam kategori â€œbaikâ€, dan tahap terakhir persentase yang diperoleh sebanyak 87,5% kategori â€œsangat baikâ€. Dari hasil yang diperoleh dapat disimpulkan bahwasannya media e-kamus materi klasifikasi tumbuhan Dicotyledoneae yang dikembangkan telah layak untuk digunakan sebagai media pembantu dalam proses pembelajaran klasifikasi makhluk hidup Kata kunci:e-kamus, website, klasifikasi tumbuhan, Dicotyledoneae